(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
Internal audit - financial and financial status of joint-stock companies is a type of service that allows close inspection, its main function regularly informing the company’s supervisory board about its activities consists of standing. The advantages of an internal audit service are that it is a company is to quickly identify the shortcomings and problems that may arise in the activity and provide a solution to it. In this thesis, we consider the issues related to the organization of the internal audit service in the joint-stock companies of our country.